(untitled) (Interdisciplinary Studies Journal, 2023)
This article arises in a timely debate about the relations between capitalism and democracy, the main objective of the article is to answer the contradictions imposed by capitalism on modern democracy. The methodological course crosses the analytical field of democratic theory, in the light of the contributions of Bobbio, Dahl, Pateman, Sartori, Schumpeter, therefore carrying out a literature review on the topic, based on the descriptors democracy, capitalism, socialism, liberalism and political participation. There is a hegemonic and counter-hegemonic perspective of democracy in capitalism, designed by the disputes of social and economic power between the social classes unleashed in the historical process and intensified with the decline of real socialism. In the context of capitalism, the concentration of wealth and inequalities tends to undermine the democratic principles of equal opportunity, equal political representation, and effective citizen participation. Economic inequality through the increasing exploitation of living labor can lead to social polarization and segregation of social actors. The critic of the hegemonic conception of liberal representative democracy designed by capitalism is urgent and historical materialism is necessary to put democracy in perspective beyond the contradictions imposed by capitalism.